Business Incubation: A Bibliometric Analysis of Global Literature - Loso Judijanto; Rani Eka Arini; Dila Padila Nurhasanah (West Science Journal Economic and Entrepreneurship, 2026)
Business incubation has become an important mechanism for supporting entrepreneurship, fostering innovation, and strengthening entrepreneurial ecosystems. However, the rapid growth of research in this field has resulted in diverse perspectives and fragmented knowledge development. This study aims to examine the intellectual structure, publication trends, influential contributions, collaboration patterns, and emerging research themes in global business incubation literature through a bibliometric analysis approach. Data were collected from the Scopus database using relevant keywords related to business incubation and business incubators. The collected publications were analyzed using bibliometric techniques, including performance analysis, citation analysis, co-authorship analysis, country collaboration analysis, keyword co-occurrence analysis, and thematic evolution mapping with the support of VOSviewer. The findings reveal that business incubation research has developed from a traditional focus on startup support toward broader perspectives involving entrepreneurship ecosystems, innovation development, technology transfer, and sustainable economic growth. The most influential studies emphasize the evolution of incubator models, technology business incubation, social capital, and incubation outcomes. The analysis also indicates that the United States, the United Kingdom, and China represent the most active contributors in shaping global research collaboration. Furthermore, keyword analysis highlights entrepreneurship, innovation, business incubators, SMEs, and technology commercialization as the dominant research themes, while recent studies increasingly explore incubation networks, digital transformation, and ecosystem-based approaches. This study contributes to the existing literature by providing a comprehensive mapping of global business incubation research and identifying future research opportunities related to digital incubation, artificial intelligence-supported entrepreneurship, and sustainable innovation ecosystems.